The Academic Study of Religion in Bibliometric Perspective - Wildman, Wesley J. (Bulletin for the study of religion, 2021)
Academic conferences are among the most energizing gatherings of scholars and scholarship. When the North American Association for the Study of Religion pivoted to an online format for their 2020 Annual Meeting, a broader audience was able to enjoy the sophisticated social analysis for which NAASR is known. In this issue, NAASR joins the Bulletin as a content-partner in publishing some of the research featured during the meeting. Wesley J. Wildman (Boston University) shares his bibliometric research of social scientific publications in the field. F. LeRon Schults (Boston University) highlights how computational modeling and simulations can be used to examine religious phenomena as well as forecast sociological dynamics. And Daniel D. Miller (Landmark College) posits a framework he calls "queer democracy" to help readers historicize, complicate, and confound the articulation of Christian nationalist politics. Together these contributions speak to currents in theory and method being explored in the North American field.